Effects of thoracic spinal thrust manipulation for the management of shoulder impingement syndrome: systematic review - Bazal Bukhari; Ashfaq Ahmad; Arooj Fatima; Sarwat Ali (Journal of the Pakistan Medical Association, 2023)
Objective: To determine the effectiveness of thoracic spinal thrust manipulation for shoulder impingement syndrome in the improvement of pain, range of motion and functional outcomes. Method: The systematic review was conducted by 2 researchers independently using search strategy developed for different databases, including Cochrane Central register of control trials, PubMed, Pedro and MEDLINE, for relevant articles published between 2008 and 2020. The search strategy was designed for each database by combining the key terms and Boolean operators related to the review’s objective. Results: Of the 312 studies identified, 14(%) were included. Of them, 4(%) were in favour of thoracic thrust manipulation, 8(%) did not support thoracic thrust manipulation as the sole treatment and 2(%) favoured thoracic thrust manipulation along with exercises. Conclusion: Studies indicated immediate improvement in range of motion as well as pain after thrust manipulation, but others reported no such clinical difference. Manipulation should be combined with other exercise therapy to ensure some clinical improvement. Key Words: Rotator cuff impingement, Rotator cuff impingement syndrome, Shoulder impingement, Shoulder impingement syndrome, Spinal manipulation.